Преобразуйте в многочлен: а) (х-2у)(х+2у)+4у^2 б) (2а-3b)(2а+3b)-3а^2 в) (5х-1)^2+10х г) (3у+4z)^2-8z(3y-2z) д) (m-2n)(m^2+2mn+4n^2)+6n^3 е) (c^2+4d)(c^4-4c^2d+16d^2)-c^2(c^4-1) ж) (3x-4y)^2-(2x-7y)(4x+2y) з) 2x(2x+3)^2-(2x-3)(4x^2+6x+9) примечание: ^2, ^3, ^4-показатели степеней

zaaz123 zaaz123    3   08.03.2019 12:10    1

Ответы
Zeus029 Zeus029  24.05.2020 05:58

а) (x-2y)(x+2y)+4y^2 = x^2-4y^2+4y^2 = x^2
б) (2a-3b)(2a+3b)-3a^2 = 4a^2-9b^2-3a^2 = a^2-9b^2
в) (5x-1)^2+10x = 25x^2-10x+1+10x = 25x^2+1
г) (3y+4z)^2-8z(3y-2z) = = 9y^2+32z^2
д) (m-2n)(m^2+2mn+4n^2)+6n^3 = m^3-2n^3
е) (c^2+4d)(c^4-4c^2d+16d^2)-c^2(c^4-1) = 64d^3+c^2
ж) (3x-4y)^2-(2x-7y)(4x+2y) = x^2+30y^2
з) 2x(2x+3)^2-(2x-3)(4x^2+6x+9) = 24x^2+18x+27

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра